2017
DOI: 10.3389/fpls.2017.00740
|View full text |Cite
|
Sign up to set email alerts
|

Saccharification Performances of Miscanthus at the Pilot and Miniaturized Assay Scales: Genotype and Year Variabilities According to the Biomass Composition

Abstract: HIGHLIGHTS Biomass production and cell wall composition are differentially impacted by harvesting year and genotypes, influencing then cellulose conversion in miniaturized assay.Using a high-throughput miniaturized and semi-automated method for performing the pretreatment and saccharification steps at laboratory scale allows for the assessment of these factors on the biomass potential for producing bioethanol before moving to the industrial scale.The large genetic diversity of the perennial grass miscanthus ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 61 publications
(94 reference statements)
1
5
0
Order By: Relevance
“…Msin could potentially be cultivated on marginal lands with higher yields and under more stressful conditions than M×g [20]. Msin genotypes also present contrasted biomass compositions which can be better adapted to different end-uses [10,[24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Msin could potentially be cultivated on marginal lands with higher yields and under more stressful conditions than M×g [20]. Msin genotypes also present contrasted biomass compositions which can be better adapted to different end-uses [10,[24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Méchin et al [28] reported that the stem digestibility of maize was negatively correlated with their Klason lignin content while the presence of ferulate was shown to impede the degradation of plant tissue [29]. In miscanthus, Belmokhtar et al [14] found that the more digestible genotypes contained higher amounts of hemicellulosic carbohydrates and lower amounts of cellulose and lignin. Van der Weijde et al [30] reported that the most important traits that contributed favorably to the saccharification efficiency of miscanthus were a high content of ferulic acid, a high ratio of p-coumaric acid to lignin and a low lignin content.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to composites, the role of CW composition and structure in saccharification efficiency is well documented for maize stover [2,12]. In miscanthus, genotype saccharification performances have been analyzed regarding the composition [13,14] and the fine structure of its CW polymers [5,15]. Saccharification efficiency is negatively correlated with lignin while the structural features of arabinoxylan and xyloglucan are found to contribute positively to hydrolysis [15].…”
Section: Introductionmentioning
confidence: 99%
“…The LANO laboratory (Saint‐Lô, France) carried out the biochemical analyses to determine cellulose, hemicellulosic carbohydrates, and lignin contents, according to a protocol adapted from that of Van Soest and Wine (1967). More details are given by Belmokhtar et al (2017). Spectra were obtained while scanning the miscanthus samples with an Antaris II NIRS analyser (ThermoScientific) providing spectra from 4000 to 10,000 cm −1 with 1557 points (4 cm −1 spacing).…”
Section: Methodsmentioning
confidence: 99%
“…These different components of the miscanthus biomass constitute an abundant source of carbon, which leads miscanthus to be currently cultivated mainly for the production of bioenergy in Europe. Combustion was initially identified as an important potential use for miscanthus (Lewandowski et al, 1995) while the production of ethanol (Belmokthar et al, 2017; van der Weijde et al, 2013) and anaerobic digestion were identified as interesting options later on (Kiesel et al, 2017; Thomas et al, 2019). Composites reinforced with miscanthus stems are being increasingly studied due to attractive mechanical properties associated with their light‐weight compared to glass fibers (Girones et al 2016).…”
Section: Introductionmentioning
confidence: 99%